Analysis of thermophysical properties of binary systems containing ethyl acetate and 1-propanol or 1-butanol - Majstorović Divna M.; Mirković Marija R.; Kijevčanin Mirjana Lj.; Živković Emila M. (Hemijska Industrija, 2020)
The aim of this research is the experimental determination of density, viscosity, refractive index and speed of sound for binary mixtures of the ester ethyl acetate and alcohols. Experimental measurements were carried out for two systems with 1-propanol and 1-butanol at atmospheric pressure and in a temperature range 288.15 - 323.15 K. Results of experimental measurements were further used to determine excess molar volumes, viscosity deviations, refractive index deviations, and excess isentropic compressibility for each investigated mixture. These calculated data were correlated using the empirical Redlich-Kister equation. Positive values of the excess molar volume and isentropic compressibility appear for both analysed systems, while values of viscosity and refractive index deviations are negative. The structure and specific characteristics of different molecules in considered mixtures and determined non-ideal behaviour allow the insight into the possible type of interactions in the mixture, interstitial accommodation and structural effects. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 172063]